Quality Characteristics of Spent Duck Sausages Containing Surimi Like Material Substitution During Refrigerated Storage - Ismail, I.; Huda , N.; Ariffin, F. (International Journal of Poultry Science, 2014)
The quality characteristics of duck sausages prepared using different treatment were evaluated. Physicochemical, sensory and microbial properties of sausages containing duck surimi-like material substitution with cryoprotectant added (CPP) and without cryoprotectant added (NPP), antioxidant added (BHA) and, duck mince (as the control, CON) were compared. CPP and NPP sample had significantly higher (p